Study on Spatial and Temporal Variation Laws of Water Yield in Forest Basin of Cold Region ——Taking Yongcui River Basin as an Example - ZHANG Lina; SUN Yingna; HU Jinhui; SHEN Zhipeng (Renmin Zhujiang)
In order to study the spatial and temporal variation laws of water yield in the forest basin of the cold region,a SWAT model was established based on the total measured runoff data of 22 years from 1994 to 2015 in Yongcui River Basin.The spatial and temporal characteristics of water yield in the basin were analyzed,and the effects of meteorological factors and land use changes on water yield were discussed.The results show that:① from 1994 to 2015,the interannual water yield in Yongcui River Basin fluctuates obviously, showing an upward trend.The annual water yield shows a unimodal distribution of increasing first and then decreasing;② the spatial distribution of water yield in Yongcui River Basin is generally high in the east and west but low in the middle.Among all land use types,the deciduous forest has the highest water yield,and the evergreen forest has the strongest water-yielding capacity;③ the area of the deciduous forest is the largest in Yongcui River Basin,and the area of forest cover is over 95%.The interannual change of land use types is not obvious,and its influence on water yield is not significant;④ the precipitation,potential evapotranspiration,and actual evapotranspiration in Yongcui River Basin show a decreasing trend in different degrees,and precipitation is the main factor influencing water yield.The results can provide a reference for the optimal allocation of water resources and ecological protection in the forest basin of the cold region.